Ethylene oxide on Pt(110) 1×2. A multimethod investigation - Weinelt, M.; Zebisch, P.; Steinrück, Hans-Peter (Chemical Physics, 1993)
The adsorption of ethylene oxide (Et-O) on the reconstructed Pt(110) 1×2 surface has been studied by TPD, LEED, work function measurements, XPS, NEXAFS, and angle-resolved UPS using linearly polarized synchrotron radiation. At temperatures below 120 K Et-O adsorbs in molecular form with a saturation coverage of ≈0.5 monolayers. Upon heating molecular desorption occurs in the temperature range from 140 to 230 K with only minor decomposition (≤0.02 monolayers), as concluded from TPD and XPS. From ARUPS and XPS the existence of two different Et-O species is inferred that are adsorbed at different adsorption sites with different local potential. The molecules are adsorbed with the oxygen end down, as concluded by the strong work function change upon adsorption (ΔΦ=-2.1 eV for the saturated layer). The polarization, polar angle and azimuthal dependence of the ARUPS spectra indicate a preferential orientation of both Et-O species with the CC axis oriented along the [110] direction and the molecular COC plane tilted towards the [001] (or [001]) azimuth. The orientation is, however, not perfect and the symmetry of the adsorption complex is C. The NEXAFS results are consistent with the proposed orientation. A detailed comparison to the results obtained for Et-O on Ni(110) in a previous study is given. © 1993.